Vapor phase synthesis of glycerol carbonate over honeycomb monolith coated with zirconia based base catalysts - Vasantha, VT; Shamshuddin, SZ Mohamed; Shyamsundar, M; Serrao, Reena Saritha; D’Souza, Joyce Queeny (Bangladesh Journal of Scientific and Industrial Research, 2018)
In this article the synthesis, characterization and catalytic activity studies of zirconia based base catalysts such as Mg(II)/ZrO2, Ca(II)/ZrO2 and Ba(II)/ZrO2 coated on honeycomb monoliths is reported. Honeycomb monoliths were coated with Mg(II)/ZrO2, Ca(II)/ZrO2, Ba(II)/ZrO2 and characterized for their physico-chemical properties such as surface basicity, crystallinity and morphology by using relevant techniques. The catalytic activity of these catalytic materials was evaluated in vapor phase synthesis of glycerol carbonate. The reaction conditions were optimized by varying reaction parameters such as nature of catalytic material, molar ratio of the reactants, catalyst bed temperature, feed-rate of the reactants and time-on-stream to obtain highest possible yield of glycerol carbonate with greater selectivity. The catalytic materials were found to be highly efficient in the synthesis of glycerol carbonate with a possible highest yield up to 98%. These catalytic materials can be easily reactivated and reused in this reaction. Bangladesh J. Sci. Ind. Res.53(1), 21-28, 2018